2017
DOI: 10.1152/jn.00742.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rapid accumulation of inhibition accounts for saccades curved away from distractors

Abstract: Saccades curved toward a distractor are accompanied by a burst of neuronal activation at the distractor locus in the intermediate layers of the superior colliculus (SCi) ~30 ms before the initiation of a saccade. Although saccades curve away from inactivated SCi loci, whether inhibition is restricted to a similar critical epoch for saccades curved away from a distractor remains unclear. We examined this possibility by modeling human saccade curvature as a function of the time between onset of a task irrelevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 37 publications
(96 reference statements)
5
21
0
Order By: Relevance
“…Interestingly, a similar spatiotemporal mechanism may elicit saccades curved away from suppressed distractor, given that a more recent study has indicated that a decrease in distractor-related neural activity in the same critical epoch is associated with saccades curved away from distractors (White et al 2012). There is also corroborating psychophysical evidence that a similar spatiotemporal mechanism elicits saccades curved toward and away from competing distractors (Kehoe and Fallah 2017). This suggests that saccade curvature is elicited simply by a transient shift in distractor-related activity either above or below that which is observed on trials with straight saccades.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Interestingly, a similar spatiotemporal mechanism may elicit saccades curved away from suppressed distractor, given that a more recent study has indicated that a decrease in distractor-related neural activity in the same critical epoch is associated with saccades curved away from distractors (White et al 2012). There is also corroborating psychophysical evidence that a similar spatiotemporal mechanism elicits saccades curved toward and away from competing distractors (Kehoe and Fallah 2017). This suggests that saccade curvature is elicited simply by a transient shift in distractor-related activity either above or below that which is observed on trials with straight saccades.…”
Section: Discussionsupporting
confidence: 59%
“…Physiological experiments have causally demonstrated that saccade curvature is due to unresolved competition immediately prior (~30 ms) to the initiation of an impending saccade in critical neural substrates for generating saccades such as SCi (McPeek et al 2003) and FEF (McPeek 2006). In fact, it is possible to elicit saccade curvature noninvasively by temporally aligning the visual onset burst of a competing distractor vector to this critical epoch (Kehoe and Fallah 2017). These effects are attributed to the spatiotemporal interaction of multiple activated saccade vector representations on retinotopic oculomotor maps in SCi (Robinson 1972) and FEF (Robinson and Fuchs 1969) in which the resulting movement is the weighted vector average of these representations and where inhibition imposes a negative contribution in the spatial average computation as saccade curvature (Aizawa and Wurtz 1998) and end points (Lee et al 1988) are directed away from the locus of collicular inactivation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the color representations in the oculomotor system almost certainly originate from cortex as the alternative retinotectal pathway is colorblind (Schiller et al, 1979 ) and the long onset latencies of color signals in SCi (~80–90 ms; White et al, 2009 ) are inconsistent with the characteristically short onset latencies of the retinotectal pathway (11–27 ms; Schiller and Malpeli, 1977 ). Furthermore, the latency differences between color and luminance signals in the oculomotor system observed either physiologically (White et al, 2009 ) or inferred from psychophysics (Kehoe and Fallah, 2017 ) are very similar to the latency differences observed between the cortical dorsal and ventral visual processing streams (Schmolesky et al, 1998 ). This suggests that color representations in the oculomotor system are processed through the ventral processing stream specifically, along which wavelength representations are transformed into perceived color representations in area V4 (Schein and Desimone, 1990 ; Conway and Livngstone, 2006 ; Conway et al, 2007 ).…”
Section: Introductionmentioning
confidence: 55%
“…The goodness-of-fits were evaluated using an F -test. If both models provided a significant fit to the data, the best fitting model was determined by performing an F -test on the ratio of the sum of squared residuals from each fitted model with n − k degrees of freedom, where k is the number of fitted parameters (see Kehoe and Fallah, 2017 ). Furthermore, to provide further evidence of a functional relationship between saccade curvature and target-distractor color space distance, we analyzed the data with a quadratic planned contrast.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation